Extreme reduction of morphological characters: a type of brachidial development found in several Late Cretaceous and Recent brachiopod species—new relationships between taxa previously listed as incertae sedis - Simon, Eric; Mottequin, Bernard (Zootaxa, 2018)
Size reduction and development of a simplified brachidial structure occurred several times during the long evolution of the Phylum Brachiopoda. Even Recent forms may be micromorphic and paedomorphic with reduced brachidia or none at all. A revision of the Maastrichtian (Late Cretaceous) Terebratella (Morrisia?) suessi Bosquet, 1859 has allowed us to erect a new genus, Jagtithyris gen. nov., because its singular brachidium development does not match any platidiid structure. Such a brachidium has also been observed in another European Late Cretaceous brachiopod, which indicates that this type was not a unique morphological curiosity. This species is the micromorphic Campanian-Maastrichtian Leptothyrellopsis polonicus Bitner & Pisera, 1979, which has brachidial structures in common with Jagtithyris suessi comb. nov., although a number of differences have been observed. The genera Leptothyrellopsis and Jagtithyris gen. nov., are included in a new family, Jagtithyrididae fam. nov. During an ongoing revision of extant brachiopod faunas we have been led to recognize a link between this family and representatives of the genus Simplicithyris Zezina, 1976. The taxonomic position of this peculiar group is also discussed.